2023
DOI: 10.3390/en16031173
|View full text |Cite
|
Sign up to set email alerts
|

Considering Forward Electricity Prices for a Hydro Power Plant Risk Analysis in the Brazilian Electricity Market

Abstract: The Brazilian Power System is mainly composed of renewable generation from hydroelectric and wind. Hence, spot and forward electricity prices tend to represent the inherently stochastic nature of these resources, while risk management is a measure taken by agents, especially hydro power plants (HPPs) to hedge against deep financial losses. A HPP goal is to maximize its profit considering uncertainties in forward electricity prices, spot prices, and generation scaling factor (GSF) for years ahead. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…It is concluded that one of the risks to be reduced is financial risks. Lauro et al [23] and Martins et al [24] identified that financial risks should be considered in energy investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is concluded that one of the risks to be reduced is financial risks. Lauro et al [23] and Martins et al [24] identified that financial risks should be considered in energy investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lauro et al [27] proposed a methodology for simulating the decision-making process for energy contracting from a hydroelectric power plant, considering uncertainties about the spot price, forward contract prices, and generation scaling factor. The authors considered the monthly prices and two-stage stochastic dynamic programming to model the uncertainty in forward prices.…”
Section: B Brazilian Electricity Spot Pricesmentioning
confidence: 99%